Actions to combat racism in football in the early decades of the 21st century (Research, Society and Development, 2021)
This essay is an attempt to rewrite and analyze the process of building of the social representations in relation to the inclusion and rise of the black players mestizo in Brazilian soccer. Initially discussed with an attempt of understand the reproduction process of social representations about racism, from the media language and cases exposed by some players who were victims of the acts. Presenting framework with the most influential actions that have been developed over the years of combat and punishment against racial acts. In conclusion that social representation about of Brazilian soccer has been transformed since the beginning of the century; however, elements of the anterior central core are still present and manifest from the moment they compare with the criticism made of white players and those made of black and mestizo players. As critics directed at whites focus mainly on the athletic, while those directed at blacks and mestizos focus on the individual; that is; they are ethnic criticism. With this, let's investigate the expressions of this act and what these attitudes cause in the lives of athletes.